Hypoglossal canal dural arteriovenous fistula embolized under precise anatomical evaluation by selective intra-arterial injection computed tomography angiography. Issue 1 (February 2015) - Kanemaru, Kazuya; Yoshioka, Hideyuki; Yagi, Takashi; Wakai, Takuma; Hashimoto, Koji; Fukumoto, Yuichiro; Suzuki, Keiko; Tateoka, Toru; Kazama, Hirofumi; Kinouchi, Hiroyuki
Dural arteriovenous fistula (DAVF) involving the hypoglossal canal is rare but increasingly reported. To achieve complete obliteration without a procedure-related complication, understanding of the precise anatomy of this DAVF is essential. Here, we describe a 72-year-old man who underwent selective intra-arterial injection computed tomography angiography which allowed us to understand the detailed anatomy of the complex DAVF regarding access routes and the target regions for transvenous embolization (TVE). With the aid of this novel neuroimaging technique successful target TVE was achieved safely and completely.